Legal regulation of false information: world and domestic experience - Tekenova, Ә.М. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The dissemination of fake news through the media and social networks, which undermines the information security of the state, the honor and dignity of citizens is an urgent issue that must be prevented through legal regulation. This problem complicates the work of a journalist in the era of current digital communications, there are lot of information noise, conflicts of interests, media wars, etc. The reputation of the media is also criticized. Therefore, it is important to know and study the world experience оf legal regulation of this sphere. Based on this, it is necessary to determine the basic methods and tools of fact checking. Misinformation, informational manipulation, fake news must be regularly monitored. The main idea of the article is the legal field of media activity in Kazakhstan and world experience in this area using the example of Western and Eastern countries.